Critical success factors of implementing shari’ah-compliant social impact bonds in Malaysia: a survey of stakeholders - Syed Azman, Syed Marwan Mujahid; Haneef, Mohamed Aslam; Engku Ali, Engku Rabiah Adawiah; Ismail, Suhaiza (2019)
Carrying out Critical Success Factors (CSFs) analysis is necessary to ensure an organisation or product can be properly developed, sustained, and managed. This paper examines the CSFs of implementing Shari’ah-compliant SIBs (SC SIB) in Malaysia. In doing so, 22 SC SIB CSFs were identified from literature review, consultation with experts, and feedback from pilot study. A survey was then conducted with stakeholders of SC SIB where 260 potential investors and developers responded. The respondents were asked to score 22 CSFs based on their perceived degree of importance on a 5-point Likert scale. Overall, the top 5 CSF in descending order of importance are: (i) Good governance framework; (ii) Fulfil ethical standards; (iii) Transparent procurement process; (vi) Well-defined scope; and (v) Viable feasibility study. While the bottom three CSFs that were ranked to a lesser degree of importance are: (i) Existing social programmes adopted; (ii) SIB Guarantor; and (iii) Political will. The findings can serve as a reference and guideline for stakeholders to develop SC SIB, not only in Malaysia, but other developing and Islamic countries as well. The CSFs reflects the stakeholders’ perspective of what they think are important for the successful development and implementation of SC SIB. The findings can also be a reference for the development of a policy framework that can be applied in the Islamic finance industry.